An Approach for Agent-Based Modeling Using AiC+ - Ngobye, Martin; Kanagwa, Benjamin; WEIDE, THEO VAN DER; Groot, Wouter T. DE (International Journal of Computing and ICT Research., 2011)
In this paper, we present AiC+, an extension of the AiC framework designed for the explanation of human actions especially in the environmental field. We use first order logics to describe the semantics used to explain the action selection of the agent (actor) using an agent hierarchy system and a fuzzy typing relation. An example is illustrated using the AiC+ to validate the framework and discuss possible future extensions to the framework.
Keywords: Action-in-context; Agent hierarchy; First order logics; Fuzzy typing relation; Involvement function